(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Central nervous system infections are common pediatric emergencies with significant morbidity and mortality. While specific infectious etiological agent being investigated and established which takes time and technical expertise, often empirical anti bacterials are started. Escalation and de-escalation follow depending on the microbiological workup, culture positivity. Knowledge of pharmacokinetic/pharmacodynamic principles of commonly used antibacterial drugs helps selection, proper dosage and duration and enables antibacterial stewardship. Different age groups of children have predictable pattern of infectious agents on epidemiological and previous microbiological work up. Forty children with aseptic meningitis/ viral meningoencephalitis with median age 15 months (95% CI 6.7 to 31.9 months) and range 1 month to 11 years are studied. There is no significant difference in the proportion of males 62.5% (95% CI 45.8 to 77.3%) and females 37.5% (95% CI 22.7 to 54.2%). All the children received Ceftriaxone I.V in a dose of 50 mg/kg 12th hourly (100 mg/kg/d). The serum and CSF Ceftriaxone levels observed are after a mean number of doses of 2.2±0.9 (range: 1 to 4 doses).